2014
DOI: 10.1177/1063426614528244
|View full text |Cite
|
Sign up to set email alerts
|

Training School Personnel to Identify Interventions Based on Functional Behavioral Assessment

Abstract: Over 15 years after passage of legislation requiring the use of functional behavioral assessment (FBA) to inform the development of positive behavior support plans (BSPs) in special education, schools are still struggling to implement BSPs based on FBA and the function of behavior. A primary concern is that school teams regularly fail to use function of behavior to generate behavioral interventions, even after completing an FBA and receiving training. The current study evaluated outcomes of an efficient 60-min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 15 publications
(26 reference statements)
1
14
0
Order By: Relevance
“…By increasing staff understanding of behavioral function and how to modify the environment to prevent and decrease challenging behavior, school personnel can begin to create a climate focused on (a) reducing the number of students who require individualized behavior support and (b) implementing with fidelity function-based interventions for students who do require that level of support (Borgmeier et al, 2014). The data from this study provide promising evidence that a typical district-level behavior specialist was able to effectively co-lead a 6-hr training series for a wide range of school professionals after receiving only minimal training from the researcher.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By increasing staff understanding of behavioral function and how to modify the environment to prevent and decrease challenging behavior, school personnel can begin to create a climate focused on (a) reducing the number of students who require individualized behavior support and (b) implementing with fidelity function-based interventions for students who do require that level of support (Borgmeier et al, 2014). The data from this study provide promising evidence that a typical district-level behavior specialist was able to effectively co-lead a 6-hr training series for a wide range of school professionals after receiving only minimal training from the researcher.…”
Section: Discussionmentioning
confidence: 99%
“…The successful implementation of individualized student support requires a team-based approach in which staff who will be implementing functionbased behavior support strategies are key contributors in the FBA and BSP design process (Benazzi, Horner, & Good, 2006). Therefore, the effectiveness and efficiency of a basic FBA/BSP approach is dependent on providing training to both school-based team-leaders and staff members who will be helping to implement individualized student supports (e.g., special and general education teachers, administrators) on how to implement a function-based approach to addressing persistent, nondangerous challenging behaviors (Borgmeier, Loman, Hara, & Rodriguez, 2014).…”
Section: Building Local Capacity For Training and Follow-up Supportmentioning
confidence: 99%
“…Effective implementation is also dependent on the second step of the assessment—implementation process—using functional assessment data to construct and then apply an assessment-based behavior intervention plan. Research has shown that, all too often, intervention plans fail to take into account valuable information provided by functional assessment (Borgmeier, Loman, Hara, & Rodriguez, 2015). Clearly, there is a need for training to help teachers develop higher quality intervention plans (Conroy, Katsiyannis, Clark, Gable, & Fox, 2002) and, more broadly, there is a need to help educators think in terms of the variables that can influence the occurrence and nonoccurrence of behavior, and especially those environmental variables that are amenable to modification (Gable, Park, & Scott, 2014).…”
Section: Remaining Challengesmentioning
confidence: 99%
“…Educational researchers in recent years have focused efforts to address these questions by refining the FBA process to make it as efficient as possible while maintaining its efficacy (McKenna, Flower, Kyung Kim, Ciullo, & Haring, 2015). This has led to the development of what is termed the "practical" or "basic" FBA (Borgmeier, Loman, Hara, & Rodriguez, 2015). The basic FBA differs from more comprehensive protocols in the depth, duration, and sophistication of preintervention analysis required.…”
Section: What: From Discipline To Instructionmentioning
confidence: 99%